Nursing management of ineffective airway clearance through effective cough technique in chronic obstructive pulmonary disease: A case study - Marlina, Serli; Epin, Epin; KK, Indra Frana Jaya; Yunianti, Fifi; Jamal, Jamal; Diana, Diana (Lentera Perawat, 2025)
Background: Ineffective airway clearance is a common complication among patients with Chronic Obstructive Pulmonary Disease (COPD), requiring structured nursing interventions such as the effective cough technique to optimize secretion mobilization. Objective: This case study aimed to describe the nursing management of ineffective airway clearance using the effective cough technique in adult COPD patients. Methods: A descriptive case study was conducted on two adult COPD patients experiencing ineffective airway clearance at RSUD Siti Fatimah. Data were collected through interviews, physical examination, direct observation, and nursing documentation over a three-day intervention period. The effective cough technique was implemented 2–3 sessions per day. Data were analyzed using descriptive analysis, comparing pre- and post-intervention respiratory parameters (RR, SpO₂, sputum characteristics) and narratively reviewing qualitative responses to evaluate clinical improvement. Results: Both patients initially exhibited dyspnea, ineffective coughing, wheezing, and difficulty expectorating thick sputum. Progressive improvements were observed across three days, demonstrated by increased sputum expulsion, decreased respiratory rate, disappearance of wheezing, improved oxygen saturation, and enhanced patient comfort. By day three, both patients were able to perform effective coughing independently and showed normalized respiratory patterns. Conclusion: The effective cough technique is a safe and clinically beneficial non-pharmacological intervention that improves airway clearance and respiratory function in COPD patients. Regular guidance, proper positioning, hydration, and continuous monitoring strengthen intervention outcomes and support patient self-management in airway clearance.